Study on the Impact of Digital Transformation on Corporate Social Responsibility - Sheng, Tianqi (Transactions on Economics, Business and Management Research, 2024)
In recent years, the rapid development of new-generation information technologies such as 5G, artificial intelligence, and blockchain has propelled the digital economy to grow vigorously. For enterprises to achieve high-quality development under such circumstances, digital transformation has become an essential path. Corporate Social Responsibility (CSR) is an evolving concept, transitioning from the initial stance of "corporations should be responsible" to the current perspective that "corporations need to proactively undertake social responsibilities." This shift reflects society's expectations of corporate roles and introduces new demands. In the strategies for sustainable corporate development, digital transformation and the fulfillment of social responsibilities are closely linked and mutually reinforcing. This connection can effectively enhance operational efficiency and market competitiveness, strengthen corporate social responsibility, and thereby realize high-quality development.